2013
DOI: 10.1080/09540121.2013.861573
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to antiretroviral treatment access for injecting drug users living with HIV in Chennai, South India

Abstract: India’s National AIDS Control Organization provides free antiretroviral treatment (ART) to people living with HIV (PLHIV), including members of marginalized groups such as injecting drug users (IDUs). To help inform development of interventions to enhance ART access, we explored barriers to free ART access at government ART centers for IDUs living with HIV in Chennai by conducting three focus groups (n = 19 IDUs) and four key informant interviews. Data were explored using framework analysis to identify categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 26 publications
5
91
0
7
Order By: Relevance
“…In that study, positive experiences reported included receiving equal treatment, being valued as a partner in one's health, social support provision, and confidentiality assurances while negative experiences included awkward interactions, irrelevant questions, rude treatment, blame, pity, excessive or differential precautions, care refusal, unnecessary referrals, delayed treatment, poor support, and confidentiality breaches. Our current findings are also similar to findings from studies that have investigated health care provision to substance users more generally [6,[36][37][38] as well as studies looking at the interactions between health care providers and substance users with HIV specifically [18][19][20]27]. For example, previous research has shown that substance users have been refused services or prescriptions [6], that substance users have been provided with less information than others and have received poorer quality care [37], and that HIV diagnoses have been provided to substance users in a detached and unsympathetic manner [18].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In that study, positive experiences reported included receiving equal treatment, being valued as a partner in one's health, social support provision, and confidentiality assurances while negative experiences included awkward interactions, irrelevant questions, rude treatment, blame, pity, excessive or differential precautions, care refusal, unnecessary referrals, delayed treatment, poor support, and confidentiality breaches. Our current findings are also similar to findings from studies that have investigated health care provision to substance users more generally [6,[36][37][38] as well as studies looking at the interactions between health care providers and substance users with HIV specifically [18][19][20]27]. For example, previous research has shown that substance users have been refused services or prescriptions [6], that substance users have been provided with less information than others and have received poorer quality care [37], and that HIV diagnoses have been provided to substance users in a detached and unsympathetic manner [18].…”
Section: Discussionsupporting
confidence: 80%
“…As our findings have shown, such attributions are not only felt by substance users with HIV but also expressed by health care providers, and the literature supports this contention [6,39,[41][42][43]. The literature also demonstrates how this discourse of agency can negatively impact the health and well-being of substance users with HIV and inhibit HIV prevention efforts [19,22,24,25,27,28,41]. Tackling such attributions of personal responsibility is thus paramount.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Globally, there has been a major challenge to engage people who inject drugs (PWIDs) in appropriate HIV treatment and care (Chakrapani, Velayudham, Shunmugam, Newman, & Dubrow, 2013; Wolfe, Carrieri, & Shepard, 2010; Zhang et al, 2011a). Specific treatment gaps exist in late testing for HIV, low uptake of antiretroviral therapy (ART), low treatment adherence, treatment discontinuation, and the burden of managing comorbidities such as hepatitis C and tuberculosis for PWID (Altice, Kamarulzaman, Soriano, Schechter, & Friedland, 2010; Lucas, Griswold, Gebo, Keruly, & Chaisson, 2006; Wolfe et al, 2010; Wood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These barriers occur at the family and social level, at the health care system level and at the individual level [72,73]. Family and social barriers to initiating ART include disenfranchisement, banishment, homelessness, social discrimination; health care system barriers include poor enabling environment, stigma and discrimination and lack of mental health and drug treatment; individual barriers including low self-esteem, poor health knowledge, and low motivation to initiate ART.…”
Section: Services For Common Mental Disorders and Substance Use Disormentioning
confidence: 99%